1994
DOI: 10.1177/001872679404700306
|View full text |Cite
|
Sign up to set email alerts
|

Organizational and Environmental Determinants of Functional and Dysfunctional Turnover: Practical and Research Implications

Abstract: This study investigates organizational and environmental determinants of functional and dysfunctional turnover. Functional turnover is negatively associated with levels of pay and unemployment and positively associated with the availability of individual incentive programs. Dysfunctional turnover is positively associated with the presence of group incentive programs and negatively associated with the presence of unions. The implications of these findings are explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
83
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(90 citation statements)
references
References 25 publications
6
83
0
1
Order By: Relevance
“…In nearly every study included here (see H. Y. Park, Ofori-Dankwa, & Bishop, 1994;Shaw et al, 2009, for exceptions), turnover rates theoretically included high, average, and low performers as well as an assortment of leavers who departed different occupational levels, thus precluding any inferences about specific employee populations. As this area progresses, developing research strategies and measures that isolate the potentially unique causes and consequences of turnover for different employee groups will be especially valuable (e.g., retaining a diverse workforce; Horn, Roberson, & Ellis, 2008).…”
Section: Future Researchmentioning
confidence: 99%
“…In nearly every study included here (see H. Y. Park, Ofori-Dankwa, & Bishop, 1994;Shaw et al, 2009, for exceptions), turnover rates theoretically included high, average, and low performers as well as an assortment of leavers who departed different occupational levels, thus precluding any inferences about specific employee populations. As this area progresses, developing research strategies and measures that isolate the potentially unique causes and consequences of turnover for different employee groups will be especially valuable (e.g., retaining a diverse workforce; Horn, Roberson, & Ellis, 2008).…”
Section: Future Researchmentioning
confidence: 99%
“…Incentive system characteristics appear to account for some of these discrepancies; for example, the use of variable pay or groupbased incentives (Guthrie, 2000;Way, 2002) has been linked with higher turnover rates, whereas the use of skill-based pay has been associated with lower turnover rates (Guthrie, 2000). In some studies, no relationship was found between collective turnover rates and performance-based rewards (Ferratt, Agarwal, Brown, & Moore, 2005;Riordan et al, 2005) or the use of group or individual incentive programs (Haines et al, 2010;Park et al, 1994). In a quasi-experiment with fast-food restaurants, Peterson and Luthans (2006) found that, relative to baseline measures, the introduction of financial incentives was associated with a 13% turnover rate reduction, while restaurants introducing nonfinancial incentives experienced a 10% reduction, and control group restaurants suffered a 5% increase.…”
Section: Hr Systems and Practicesmentioning
confidence: 99%
“…Turnover is an important aspect for organizations because it is a determining factor of organizational effectiveness (Park et al 1994). It is also important to note that turnover can be predicted through turnover intentions or the intention to leave (Jaros 1997;Vandenberg and Nelson 1999).…”
Section: Hr Attributions and Turnover Intentionmentioning
confidence: 99%